Comparative analysis of the anticorrosive properties of trivalent chromium conversion coatings formed on 2024-T3 and 2024-T351 aluminium alloys. (1st May 2020) - Verdalet-Guardiola, X.; Saillard, R.; Fori, B.; Duluard, S.; Blanc, C.
Graphical abstract: Highlights: TCP coated AA2024-T3 had better corrosion resistance than AA2024-T351. The corrosion behaviour of TCP coated samples depended on the surface Cu coverage. High surface Cu coverage θCu led to thicker and/or more defective coatings. The dealloying of large Cu-rich IMCs could lead to Cu-rich sponges, then high θCu . A defective coating formed at grain boundaries decorated by Cu-rich precipitates. Abstract: The anticorrosive properties of the trivalent chromium process (TCP) coatings were studied for a 2024 aluminium alloy (AA2024) in both T3 and T351 metallurgical states. Better corrosion resistance was measured for the TCP coated AA2024-T3 compared to AA2024-T351, which was clearly related to the surface copper coverage measured after the pre-treatments for the different samples. The differences were explained considering the reactivity of both the S-phase coarse intermetallics (IMCs) and intergranular Cu-rich precipitates during deoxidation. Large S-phase IMCs and numerous intergranular Cu-rich precipitates constituted critical metallurgical parameters for the anticorrosive properties of the TCP coatings.